Peran Mediasi Dukungan Organisasi yang Dirasakan dalam Hubungan antara Kualitas Hidup Kerja, Konflik Kerja–Keluarga, dan Niat Berpindah Kerja di Sektor Kesehatan - Fatma Pramesti, Ayunda; Akhmad Darmawan; Naelati Tubastuvi; Purnadi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines employee retention issues in healthcare institutions, focusing on the effects of Quality of Work Life (QWL) and Work–Family Conflict (WFC) on Turnover Intention (TI) with Perceived Organizational Support (POS) as a mediator. A cross-sectional survey was conducted on 115 hospital employees using purposive sampling, and data were analyzed with PLS-SEM. The results indicate that QWL negatively affects TI and positively influences POS, while WFC positively affects TI but does not influence POS. POS negatively affects TI and mediates the relationship between QWL and TI. These findings highlight the importance of improving QWL to strengthen perceived support and reduce turnover intention.